Sams teach yourself SQL in 24 hours - Stephens, Ryan K. (Sams teach yourself., 2008)
Fully updated for the most recent SQL standards, this essential book teaches SQL quickly and easily for those with little or no programming experience. Each chapter builds on the previous one with real-world examples and hands-on exercises.